2009
DOI: 10.1590/s0103-50532009000900026
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of L929 mouse ribroblast cells on poly(styrene)/poly(methyl methacrylate) films

Abstract: Filmes de poli(estireno) (PS), poli(metacrilato de metila) (PMMA), blenda de PS/PMMA (1:1) e copolímero PS-b-PMMA foram preparados e avaliados quanto à adesão celular usando fibroblastos de camundongos L929. Embora todos os filmes poliméricos tenham se mostrado bons substratos para o crescimento e proliferação celular, estes processos foram levemente favorecidos na blenda PS:PMMA. O número e a morfologia foram idênticos para cultura de células nos filmes e na lamínula de vidro ou na placa de plástico. A caract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…2(A and B) are in agreement with data published in the literature [26], and are promising in terms of the potential use of the PS/PMMA blend in biomedical applications. Some factors such as the surface wettability of polymer films can influence the adhesion and proliferation of cells, since the first layer of the cell that touches the surface is comprised of water [10,11].…”
Section: In Vitro Cytotoxicitysupporting
confidence: 89%
See 3 more Smart Citations
“…2(A and B) are in agreement with data published in the literature [26], and are promising in terms of the potential use of the PS/PMMA blend in biomedical applications. Some factors such as the surface wettability of polymer films can influence the adhesion and proliferation of cells, since the first layer of the cell that touches the surface is comprised of water [10,11].…”
Section: In Vitro Cytotoxicitysupporting
confidence: 89%
“…in the blend) [26]. Considering this result, the aim of the study reported herein was to verify the advantages of using this film as a biomaterial.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 93%
See 2 more Smart Citations
“…Similar results have been depicted in scanning microscopy images and described in literature. [23][24][25][26] For the microscopy experiments, the dish bottoms were not treated.…”
Section: Segmentation Of a Cell's Focal Regionmentioning
confidence: 99%